A Gender-based Analysis of Observance and Non-Observance of Conversational Maxims in Front Office Students’ Speech at Mediterranean College in Academic Year 2015/2016 - ., NI MADE AYU PURNAMI; ., PROF. DR. I NYM. ADI JAYA PUTRA, M.A.; ., PROF. DR. PUTU KERTI NITIASIH, M.A. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
Penelitian ini bertujuan untuk menyelidiki, mendeskripsikan dan menjelaskan bagaimana maxim percakapan diobservasi oleh siswa-siswa Front Office di Mediterranean College ketika mereka praktek bekerja sebagai staff Front Office dan jenis maxims non-observance apa yang dihasilkan oleh siswa-siswa Front Office dalam mengobservasi maxim percakapan dalam kaitannya dengan kesopanan. Subjek penelitian adalah siswa-siswa Front Office di Mediterranean College. Data untuk penelitian kualitatif ini dikumpulkan melalui observasi dan wawancara yang kemudian dianalisa dengan menggunakan teori Cooperative Principle dari Paul Grice?s (1975). Penelitian ini menemukan bahwa baik siswa laki-laki dan perempuan menghasilkan persentase tinggi dalam mengobservasi maxim of quantity (45.09%) untuk persentase siswa laki-laki dan (55.71%) untuk persentase siswa perempuan. Penelitian ini juga menemukan bahwa maxim of quantity adalah maxim dominan yang diobservasi oleh siswa-siswa front office di Mediterranean College. Hal terpenting yakni membangun sebuah percakapan seinformatif sebagaimana yang diperlukan. Penelitian menunjukkan bahwa siswa-siswa Front Office mengobservasi maxim percakapan dalam melakukan reservasi. Penelitian ini menunjukkan bahwa siswa-siswa front office laki-laki dan perempuan menghasilkan persentase tinggi dari maxim of quantity guna membangun percakapan seinformatif sebagaimana yang diperlukan. Kata Kunci : Maxims Percakapan, Gender, Observance of maxims, Non-observance of maxims, Kesopanan This study was intended to investigate, describe and explain how conversational maxims are observed by the Front Office Students at Mediterranean College when they do the practice as Front Office Staff and what types of non-observance are committed by the Front Office Students in observing conversational maxims in relation to politeness. The subjects were the Front Office students of Mediterranean College. The data for this qualitative study were collected through observation and interviews which were then analyzed by using Paul Grice?s (1975) Cooperative Principle theory. The study showed that the Front Office students observed conversational maxims in certain part of handling table reservation. This study found that both male and female students produced high percentage of observing maxim of quantity (45.09%) of male students percentage and (55.71%) of female students percentage. This study also found that maxim of quantity was the dominant maxim observed by the front office students at Mediterranean College. The point was making a conversation as informative as is required. The study showed that both male and female front office students produced highest percentages of maxim of quantity in order to make the conversation informative as is required. keyword : Conversational maxims, Gender, Observance of maxims, Non-observance of maxims, Politeness